Education for the 21st century: Heading off in various directions - Stanojević Dobrivoje (Visoka škola strukovnih studija za vaspitače, Kruševac, 2013)
This paper claims that education in Serbia, shaped under strong outside influence of politics, as often as not, pays the price of social prominence and aristocratic spirit in decline. The investigation then goes on to investigate the assumptions underlying modern upbringing, also dealing with pedagogic skills and traits of contemporary educational style. It ends with the conclusion that a contemporary educator should be as close as possible to real life. He should be a committed alchemist of the future.